Those Who Serve - Tufts, Steven (Labour / Le Travail, 2007)
The article reviews and comments on three books including "Paradise Laborers: Hotel Work in the Global Economy," by Patricia Adler and Peter Adler, "Class Acts: Service and Inequality in Luxury Hotels," by Rachel Sherman, and "Differences That Matter: Social Policy and the Working Poor in the United States and Canada," by Dan Zuberi.
Keywords: ADLER; Patricia; ADLER; Peter; BOOKS – Reviews; CLASS Acts: Service & Inequality in Luxury Hotels (Book); DIFFERENCES That Matter: Social Policy & the Working Poor in the United States & Canada (Book); Nonfiction; PARADISE Laborers: Hotel Work in the Global Economy (Book); SHERMAN; Rachel; ZUBERI; Dan